Cerebellar tumefactive demyelination in MOGAD: a case report on diagnostic challenges and immunotherapeutic strategy - Zheng, XiaoDan; Zhang, JiaYue; Li, DaWei; Yuan, Bo (Frontiers in Immunology, 2026)
Tumefactive demyelination is a rare phenotypic subtype of myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD) and poses significant diagnostic challenges due to substantial clinical and radiological overlap with intracranial neoplasms and other demyelinating conditions. This mimicry frequently leads to misdiagnosis and subsequent inappropriate therapeutic interventions and delay in treatment, thereby increasing the risk of adverse clinical outcomes. We present the case of a 31-year-old male with a prior history of MOG-associated optic neuritis (ON) who developed acute-onset dizziness and gait instability evolving over five days. Brain magnetic resonance imaging (MRI) demonstrated an atypical mass-like lesion in the left cerebellar hemisphere with extension to the middle cerebellar peduncle. Serum testing showed MOG-IgG positivity at 1:100 titer (live cell-based assay) with negative AQP4-IgG. Following timely pulse corticosteroid therapy, the patient showed marked symptomatic improvement and received sequential maintenance of oral corticosteroid for six months. A follow-up MRI revealed complete resolution of abnormalities, and no recurrence was observed during the 21-month follow-up period. This case highlights the critical importance of including rare tumefactive MOGAD in the differential diagnosis of mass-like lesions, thereby avoiding the potential morbidity associated with misdiagnosis and delayed treatment. It also underscores the role of maintenance therapy in reducing relapses and preventing disability accumulation.